High-risk obstetrics, maternal death - Gonzáles del Riego Burga, Manuel (2015)
By taking the highest risk of life to appreciate chances of damage during pregnancy and the perinatal period it is to measure additional risks to the pregnancy itself. For this reason it is accepted that maternal mortality is also a risk index and quality of care in relation to resources, coverage, and professional training levels. This approach, however, does not invalidate its clinical and social significance, because depending on the study area may be the first or second cause of death for women 25-34 years old; in many developing countries that have this information (Rayston, 1977), paradoxically from an epidemiological point of view, they would be less risky age.